The effect of hemodialysis on accelerated atherosclerosis in diabetic patients: correlation of carotid artery intima-media thickness with oxidative stress - ÖZBEN SADIÇ, BESTE (ELSEVIER SCIENCE INC, 2009)
Objective: Both diabetes and hemodialysis (HD) are associated with increased oxidative stress. The aim of this study was to clarify the effect of maintenance HD on oxidative stress parameters in diabetic patients and to explore any relation between carotid artery intima-media thickness (CIMT) and oxidative stress markers. Methods: Twenty Type 2 diabetic patients undergoing chronic maintenance HD, 20 type 2 diabetic patients with normal renal function, and 20 age- and sex-matched healthy subjects were included. Serum thiobarbituric acid reactive substances (TBARS), protein carbonyl content (PCO), and nitrite/nitrate levels were determined as oxidative stress markers. Serum vitamin E, plasma sulfhydryl (P-SH), erythrocyte glutathione (GSH) levels, and superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) activities were measured as antioxidants. CIMT was assessed by carotid artery ultrasonography. Results: Both diabetic patient groups had enhanced oxidative stress indicated by higher levels of TBARS, PCO, and nitrate/nitrite and lower activities of SOD, CAT, and GPx compared to controls. Diabetic patients undergoing HD had significantly higher CIMT (P=.001) and higher levels of nitrite/nitrate (P=.05), PCO (P=.03), and GSH (P=.04) but significantly lower levels of P-SH (P <.001), serum vitamin E (P=.04), SOD (P=.02), CAT (P=.001), and GPx (P=.006) compared to diabetic patients with normal renal functions. There were significant negative correlations between CIMT and SOD (r=-0.50, P <.001), CAT (r=-0.41, P=.003), and P-SH levels (r=-0.51, P <.001) and significant positive correlation between CIMT and nitrite/nitrate levels (r=0.41, P=.003) and TBARS (r=0.35, P=.02). Linear regression analysis showed TBARS was significantly and positively correlated with CIMT (P=.04), while SOD and P-SH were significantly and negatively correlated with CIMT (P=.05 and P=.02, respectively). Conclusions: Hemodialysis exacerbates oxidative stress and disturbances in antioxidant enzymes in diabetic patients. Serum nitrite/nitrate and TBARS can be used as positive determinants, while erythrocyte SOD, CAT activities, and P-SH level can be used as negative determinants of atherosclerosis assessed by CIMT in diabetic patients. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Diabetes; Chronic hemodialysis; Oxidative stress; Carotid artery intima-media thickness; CARDIOVASCULAR RISK-FACTORS; MYOCARDIAL-INFARCTION; WALL THICKNESS; MELLITUS; DISEASE; PREDICTION; STROKE; ASSAY